Genome-Wide Association Study Implicates Testis-Sperm Specific FKBP6 as a Susceptibility Locus for Impaired Acrosome Reaction in Stallions - Raudsepp, Terje; McCue, Molly E.; Das, Pranab J.; Dobson, Lauren; Vishnoi, Monika; Fritz, Krista L.; Schaefer, Robert; Rendahl, Aaron K.; Derr, James N.; Love, Charles C.; Varner, Dickson D.; Chowdhary, Bhanu P. (PLOS Genetics, 2012)
Impaired acrosomal reaction (IAR) of sperm causes male subfertility in humans and animals. Despite compelling evidence about the genetic control over acrosome biogenesis and function, the genomics of IAR is as yet poorly understood, providing no molecular tools for diagnostics. Here we conducted Equine SNP50 Beadchip genotyping and GWAS using 7 IAR–affected and 37 control Thoroughbred stallions. A significant (P<6.75E-08) genotype–phenotype association was found in horse chromosome 13 in FK506 binding protein 6 (FKBP6). The gene belongs to the immunophilins FKBP family known to be involved in meiosis, calcium homeostasis, clathrin-coated vesicles, and membrane fusions. Direct sequencing of FKBP6 exons in cases and controls identified SNPs g.11040315G>A and g.11040379C>A (p.166H>N) in exon 4 that were significantly associated with the IAR phenotype both in the GWAS cohort (n = 44) and in a large multi-breed cohort of 265 horses. All IAR stallions were homozygous for the A-alleles, while this genotype was found only in 2% of controls. The equine FKBP6 was exclusively expressed in testis and sperm and had 5 different transcripts, of which 4 were novel. The expression of this gene in AC/AG heterozygous controls was monoallelic, and we observed a tendency for FKBP6 up-regulation in IAR stallions compared to controls. Because exon 4 SNPs had no effect on the protein structure, it is likely that FKBP6 relates to the IAR phenotype via regulatory or modifying functions. In conclusion, FKBP6 was considered a susceptibility gene of incomplete penetrance for IAR in stallions and a candidate gene for male subfertility in mammals. FKBP6 genotyping is recommended for the detection of IAR–susceptible individuals among potential breeding stallions. Successful use of sperm as a source of DNA and RNA propagates non-invasive sample procurement for fertility genomics in animals and humans.